2001
DOI: 10.4049/jimmunol.167.7.4046
|View full text |Cite
|
Sign up to set email alerts
|

Loss of IFN-γ Production by Invariant NK T Cells in Advanced Cancer

Abstract: Invariant NK T cells express certain NK cell receptors and an invariant TCRalpha chain specific for the MHC class I-like CD1d protein. These invariant NK T cells can regulate diverse immune responses in mice, including antitumor responses, through mechanisms including rapid production of IL-4 and IFN-gamma, but their physiological functions remain uncertain. Invariant NK T cells were markedly decreased in peripheral blood from advanced prostate cancer patients, and their ex vivo expansion with a CD1d-presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(140 citation statements)
references
References 43 publications
(28 reference statements)
5
130
2
Order By: Relevance
“…It is also reported that the cytokine profile of NKT cells skews from IFN-γ dominant toward IL-4 dominant in advanced prostate cancer patients. The skewing of NKT cell cytokine profile toward IL-4 is associated with poor prognosis and decreased survival [39]. Herein, we examined if chronic alcohol consumption alters the cytokine profile of iNKT in the melanoma-bearing mice at the late stage of tumor growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also reported that the cytokine profile of NKT cells skews from IFN-γ dominant toward IL-4 dominant in advanced prostate cancer patients. The skewing of NKT cell cytokine profile toward IL-4 is associated with poor prognosis and decreased survival [39]. Herein, we examined if chronic alcohol consumption alters the cytokine profile of iNKT in the melanoma-bearing mice at the late stage of tumor growth.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that continuous activation induces iNKT cell anergy and that the anergic iNKT cells retain the function to produce IL-4 but are unable to produce IFN-γ [43, 44]. This phenomenon was also found in advanced prostate cancer patients [39]. We hypothesize that in the melanoma-bearing mice Signal I and Signal II continuously stimulate iNKT cells thus inducing iNKT cell anergy and that the Th2-dominant cytokine profile inhibits antitumor immunity and enhances tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of those patients with low IFNγ production showed no clinical effects (Motohashi et al, 2011). Additionally, decreased NKT cell numbers and impaired IFNγ productions have been reported previously in cancer patients and are related to poor clinical outcome (Molling et al, 2007;Motohashi et al, 2011;Muhammad Ali Tahir et al, 2001). Thus, optimal IFNγ production is important for the antitumor effects of NKT cells.…”
Section: Introductionmentioning
confidence: 92%
“…Recent clinical trials evaluating the effectiveness of NKT cell based immunotherapy in treating patients with solid tumors in the liver or lung, as well as unresectable head and neck cancers, have shown some promise (Ishikawa et al, 2005; Uchida et al, 2008). Collectively, these studies and others (Kawano et al, 1999b; Tahir et al, 2001; Fujii et al, 2003a) have demonstrated that many cancer patients have a deficiency in both NKT cell number and function, which suggests that in vivo NKT cell modulation would only be effective in patients with sufficient numbers of functional NKT cells.…”
Section: Introductionmentioning
confidence: 80%